Zn monatomic modified hard carbon material as well as preparation method and application thereof

By modifying the hard carbon material by Zn single atom, Zn-N4 carbon nanosheets were prepared as the negative electrode material for sodium ion batteries, which solved the shortcomings of existing materials in Coulomb efficiency, rate performance and cycle stability, and realized the sodium ion battery. Efficient and stable application.

CN119390056AActive Publication Date: 2025-02-07JILIN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411506495.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing sodium ion battery materials have problems such as low initial Coulomb efficiency, poor rate performance, and poor cycle stability, which lead to difficulties in large-scale applications.

Method used

Zn single atom modified hard carbon material is used to prepare zinc-containing precursors by high-energy ball milling method, and carbonize at high temperature to form Zn-N4 carbon nanosheets as the negative electrode material for sodium ion batteries.

Benefits of technology

It significantly improves the reversible capacity, rate performance and cycle life of sodium ion batteries, ensuring high efficiency and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390056A_ABST
    Figure CN119390056A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of sodium ion batteries, and provides a Zn monatomic modified hard carbon material and a preparation method and application thereof.The preparation method comprises the steps that an electrode plate is prepared through a Zn-N4 carbon nanosheet, and the electrode plate is cut to obtain a circular electrode plate; the circular electrode plate is used as a negative electrode, a metal sodium plate is used as a counter electrode, and the sodium ion battery is assembled together with a diaphragm and electrolyte. The Zn-N4 carbon nanosheet prepared by the invention is used as a sodium ion battery negative electrode material, and shows extremely high reversible capacity (321.4 mAh g <-1 > under 0.05 A g <-1 >), excellent rate capability (190.2 mAh g <-1 > under 5A g <-1 >) and ultra-long cycle life (the capacity is maintained at 92.1% after 4000 cycles under 2A g <-1 >). The monatomic modification method provided by the invention provides a reasonable and effective solution for challenges of slow storage dynamics and poor cycling stability of the anode of the sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a Zn single atom modified hard carbon material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are considered as the next generation of emerging energy storage devices with great potential due to their abundant sodium reserves and similar chemical properties to lithium. Although graphite is currently widely used as a carbonaceous anode material, its shortcomings such as small interlayer spacing and easy formation of unstable compounds with sodium limit its large-scale application in sodium-ion batteries. In contrast, hard carbon materials are considered to be one of the most promising anode candidate materials due to their low voltage platform, chemical stability, low cost and easy preparation.

[0003] The existing technology introduces defects and functional groups, increases the specific surface area and other modification strategies to increase the adsorption capacity contribution of sodium ions. However, these modification strategies also have some problems, such as irreversible adsorption of defect sites and irreversible decomposition of electrolyte, which will form an uneven solid electrolyte interface (SEI), resulting in low initial coulombic efficiency, poor rate performance, unsatisfactory cycle stability and other problems in sodium ion batteries. For this reason, the present invention proposes Zn single atom modified hard carbon material and its preparation method and application. Summary of the invention

[0004] The purpose of the present invention is to provide a Zn single atom modified hard carbon material and a preparation method and application thereof, aiming to solve the problems raised in the above background technology.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The method for preparing a Zn single atom modified hard carbon material comprises the following steps:

[0007] Weigh dicyandiamide, benzenetricarboxylic acid, zinc oxide and ammonium nitrate and put them into a ball mill; mix the raw materials evenly and grind them; after grinding, centrifuge the resulting product, then wash it with ethanol, and then dry it in a vacuum oven to obtain a precursor; place the precursor in high-purity argon gas and perform high-temperature carbonization to obtain the final product, which is recorded as Zn-N4 carbon nanosheets.

[0008] Furthermore, the dicyandiamide is replaced by melamine or urea; the ammonium nitrate is replaced by N,N-dimethylformamide or ethanol; the zinc oxide is replaced by zinc chloride, zinc nitrate, zinc acetylacetonate, cobalt trioxide, nickel trioxide, antimony trioxide or molybdenum trioxide.

[0009] Further, the following specific steps are included:

[0010] Weigh 6 g of dicyandiamide, 0.6 g of benzenetricarboxylic acid, 108 mg of zinc oxide and 50 mg of ammonium nitrate and put them into a ball mill; mix the raw materials evenly and grind them at a speed of 500 rpm for 2 hours; after grinding, the resulting product is centrifuged, then washed three times with ethanol, and then dried in a vacuum oven at 60°C for 12 hours to obtain a precursor; the precursor is placed in high-purity (99.99%) argon gas and high-temperature carbonized at 800°C for 2 hours to obtain the final product, which is recorded as Zn-N4 carbon nanosheets.

[0011] The Zn single atom modified hard carbon material is prepared according to the above-mentioned preparation method of the Zn single atom modified hard carbon material.

[0012] According to the above-mentioned application of Zn single atom modified hard carbon material in the preparation of sodium ion batteries.

[0013] Furthermore, the sodium ion battery is prepared according to the following steps:

[0014] Electrode sheets were prepared using Zn-N4 carbon nanosheets, which were cut into circular electrode sheets with a diameter of 12 mm. The circular electrode sheets were used as negative electrodes, and the metallic sodium sheets were used as counter electrodes, and were assembled together with a separator and an electrolyte into a sodium ion battery.

[0015] Furthermore, the specific process of the step of preparing the electrode sheet using Zn-N4 carbon nanosheets is as follows:

[0016] Zn-N4 carbon nanosheets were mixed with a binder and a conductive agent in a ratio of 8:1:1, N-methylpyrrolidone was used as a solvent, and the mixture was stirred thoroughly to form a slurry. The slurry was coated and placed in a vacuum drying oven, and dried at 60° C. to obtain an electrode sheet.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The Zn-N4 carbon nanosheets prepared by the present invention are used as negative electrode materials for sodium ion batteries and exhibit extremely high reversible capacity (0.05Ag -1 321.4mAh g -1 ), excellent rate performance (5Ag -1 190.2mAh g -1 ) and ultra-long cycle life (at 2A g -1 The capacity was retained at 92.1% after 4000 cycles. The single-atom modification method proposed in the present invention provides a reasonable and effective solution to the challenges of slow anode storage kinetics and poor cycle stability of sodium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1Scanning electron microscopy (SEM) characterization of Zn-N4 carbon nanosheets.

[0020] Figure 2 X-ray diffraction (XRD) characterization of Zn-N4 carbon nanosheets.

[0021] Figure 3 Transmission electron microscopy (TEM) characterization of Zn-N4 carbon nanosheets.

[0022] Figure 4 This is the element distribution map of Zn-N4 carbon nanosheets.

[0023] Figure 5 High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of Zn-N4 carbon nanosheets.

[0024] Figure 6 N1s and Zn 2p images of X-ray photoelectron spectroscopy (XPS) of Zn-N4 carbon nanosheets.

[0025] Figure 7 X-ray absorption fine structure (XAFS) characterization of Zn-N4 carbon nanosheets; (a) is the near-edge absorption structure spectrum, (b) is the extended-edge absorption structure spectrum, and (c) is the extended-edge structure fitting curve.

[0026] Figure 8 Characterization of the cyclic voltammetry curves of Zn-N4 carbon nanosheets as the negative electrode of sodium ion batteries.

[0027] Fig. 9 Characterization of the rate performance of Zn-N4 carbon nanosheets as negative electrode for sodium ion batteries.

[0028] Fig.10 Characterization of the cycling performance of Zn-N4 carbon nanosheets as negative electrode for sodium ion batteries. DETAILED DESCRIPTION

[0029] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of the present invention. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials can be obtained from commercial sources unless otherwise specified.

[0030] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0031] Example 1, preparation of Zn-N4 carbon nanosheets;

[0032] First, 6g of dicyandiamide, 0.6g of benzenetricarboxylic acid, 108mg of zinc oxide and 50mg of ammonium nitrate were accurately weighed and placed in a ball mill; the raw materials were mixed evenly and ground at 500 rpm for 2h; after grinding, the resulting product was centrifuged and then washed three times with ethanol to remove impurities. Then it was dried in a vacuum oven at 60°C for 12h to obtain a precursor. The precursor was placed in high-purity argon and carbonized at 800°C for 2h to obtain the final product, which was named Zn-N4 carbon nanosheets.

[0033] In an embodiment of the present invention, the present invention uses a high-energy ball milling method to prepare a zinc-containing precursor. In this process, the combined action of the lateral shear force and the vertical extrusion pressure destroys the zinc-oxygen bonds in zinc oxide, converting them into molten zinc ions, which then cooperate with benzene trimeric acid to self-assemble into a zinc-based metal organic framework (MOF). In the subsequent high-temperature pyrolysis process, the zinc ions are reduced to metallic zinc by carbon and volatilize in a gaseous form. The volatilized single atoms are captured and anchored on the carbon support by four nitrogen atoms on the carbon support to form Zn-N4 carbon nanosheets. The advantages of Zn-N4 carbon nanosheets include:

[0034] 1) Increase Na + The storage capacity of Na + The reversible adsorption / desorption at complementary atomic sites and the improvement in electrical conductivity enhance the charge transfer kinetics between these sites, leading to improved storage capacity.

[0035] 2) Reduce the diffusion barrier: The optimized electrode surface configuration improves ion affinity and reduces ion migration resistance, thereby accelerating ion storage kinetics and significantly improving the rate performance of electrode materials.

[0036] 3) Construction of a robust SEI: Single-atom sites significantly enhance the redox activity of the electrode surface and can catalyze the preferential decomposition of electrolyte salts to form a uniform, stable, and inorganic-rich SEI, thereby effectively preventing further decomposition of the electrolyte and the occurrence of side reactions.

[0037] Example 2, preparation of sodium ion battery;

[0038] Zn-N4 carbon nanosheets are mixed with polyvinylidene fluoride (PVDF) and a conductive agent (superP) in a ratio of 8:1:1, and N-methylpyrrolidone (NMP) is used as a solvent. The mixture is stirred thoroughly to form a slurry. The slurry is coated and placed in a vacuum drying oven, and dried at 60°C to obtain an electrode sheet. The electrode sheet is cut to obtain a circular electrode sheet with a diameter of 12 mm. The circular electrode sheet is used as the negative electrode, and the metal sodium sheet is used as the counter electrode, and they are assembled together with a diaphragm and an electrolyte to form a sodium ion battery.

[0039] Example 3, various characterizations and performance tests of Zn-N4 carbon nanosheets;

[0040] Scanning electron microscopy (SEM) characterization: Results are shown in Figure 1 , it can be seen that the prepared material is a stacked nanosheet structure.

[0041] X-ray diffraction (XRD) characterization: Results are shown in Figure 2 It can be seen that the XRD diffraction peak of the prepared material has only a broad peak of carbon at about 2θ=26°, and there is no characteristic diffraction peak of Zn, indicating that Zn is distributed in an amorphous state.

[0042] Transmission electron microscopy (TEM) characterization: Results are shown in Figure 3 , the carbon sheets are wrinkled and have a layered structure. Figure 4 This is an element distribution diagram, which shows that carbon, nitrogen, oxygen and zinc are evenly distributed.

[0043] High-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images: Results are shown in Figure 5 The dense bright spots in the figure are single Zn atoms, which intuitively show the distribution of Zn on the amorphous carbon carrier.

[0044] X-ray photoelectron spectroscopy (XPS) images of N1s and Zn 2p: Results are shown in Figure 6 , indicating that single-atom Zn is bound to N, which is consistent with the results of HAADF-STEM.

[0045] X-ray absorption fine structure (XAFS) characterization: Results are shown in Figure 7 In (a), the near-edge absorption threshold of Zn-N4 carbon nanosheets is between that of Zn foil and ZnO and close to that of ZnO, proving that it exists in a valence state close to +2. Figure 7 The EXAFS spectrum in (b) shows that Zn single atoms are bound to N. Figure 7 The fitting data in (c) further confirm the existence of the ZnN4 configuration, in which a single Zn atom is stabilized by bonding with four surrounding nitrogen atoms.

[0046] Cyclic voltammetry curve characterization as a negative electrode for sodium ion batteries: Results are shown in Figure 8 , at 0.1mV s -1 At a scan rate of 1.5 V, the voltage window was 0.01-3.0 V. During the first cycle, the irreversible reduction peak appeared, indicating the formation of the solid electrolyte interface.

[0047] Characterization of rate performance as a negative electrode for sodium ion batteries: Results are shown in Fig. 9 , at 0.05Ag -1 At a current density of 3.34 mAh g, the sodium half-cell has a reversible capacity of 321.4 mAh g -1, and in 5Ag -1 At high current density, the capacity can still be maintained at 190.2mAhg -1 .

[0048] Cycling performance characterization as a negative electrode for sodium ion batteries: Results are shown in Fig.10 , in 2Ag -1 At a current density of , after 4000 charge and discharge tests, the capacity retention rate was 92.1%.

[0049] Conclusion: The Zn-N4 carbon nanosheets prepared in this invention exhibit extremely high reversible capacity (0.05A g -1 321.4mAh g -1 ), excellent rate performance (5A g -1 190.2mAh g -1 ) and ultra-long cycle life (at 2Ag -1 The capacity was retained at 92.1% after 4000 cycles. The single-atom modification method proposed in the present invention provides a reasonable and effective solution to the challenges of slow anode storage kinetics and poor cycle stability of sodium-ion batteries.

[0050] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing a Zn single atom modified hard carbon material, characterized in that: The following steps are involved: Weigh dicyandiamide, benzenetricarboxylic acid, zinc oxide and ammonium nitrate and put them into a ball mill; mix the raw materials evenly and grind them; After grinding, the product is centrifuged, washed with ethanol, and then dried in a vacuum oven to obtain a precursor; the precursor is placed in high-purity argon gas for high-temperature carbonization to obtain the final product, which is recorded as Zn-N4 carbon nanosheets.

2. The method for preparing a Zn single atom modified hard carbon material according to claim 1, characterized in that: The dicyandiamide is replaced by melamine or urea; the ammonium nitrate is replaced by N,N-dimethylformamide or ethanol; the zinc oxide is replaced by zinc chloride, zinc nitrate, zinc acetylacetonate, cobalt trioxide, nickel trioxide, antimony trioxide or molybdenum trioxide.

3. The method for preparing a Zn single atom modified hard carbon material according to claim 1, characterized in that: The specific steps include: Weigh 6 g of dicyandiamide, 0.6 g of benzenetricarboxylic acid, 108 mg of zinc oxide and 50 mg of ammonium nitrate and put them into a ball mill; mix the raw materials evenly and grind them at a speed of 500 rpm for 1-5 hours; After grinding, the product was centrifuged, washed three times with ethanol, and then dried in a vacuum oven at 60°C for 12 hours to obtain a precursor; the precursor was placed in argon gas with a purity of 99.99% and carbonized at 800°C for 2 hours to obtain the final product, which was recorded as Zn-N4 carbon nanosheets.

4. A Zn single atom modified hard carbon material obtained according to the method for preparing a Zn single atom modified hard carbon material according to any one of claims 1 to 3.

5. Use of the Zn single atom modified hard carbon material according to claim 4 in the preparation of sodium ion batteries.

6. The use of the Zn single atom modified hard carbon material in the preparation of a sodium ion battery according to claim 5, characterized in that: The sodium ion battery is prepared according to the following steps: Electrode sheets were prepared using Zn-N4 carbon nanosheets, which were cut into circular electrode sheets with a diameter of 12 mm. The circular electrode sheets were used as negative electrodes, and the metallic sodium sheets were used as counter electrodes, and were assembled together with a separator and an electrolyte into a sodium ion battery.

7. The use of the Zn single atom modified hard carbon material in the preparation of a sodium ion battery according to claim 6, characterized in that: The specific process of the step of preparing the electrode sheet using Zn-N4 carbon nanosheets is as follows: Zn-N4 carbon nanosheets were mixed with a binder and a conductive agent in a ratio of 8:1:1, N-methylpyrrolidone was used as a solvent, and the mixture was stirred thoroughly to form a slurry. The slurry was coated and placed in a vacuum drying oven, and dried at 60° C. to obtain an electrode sheet.

Citation Information

Patent Citations

  • Cobalt monatomic / nitrogen-doped mesoporous carbon fiber material as well as preparation method and application thereof

    CN114308094A

  • Metal-N4 doped carbon catalyst with high oxygen reduction performance and preparation method thereof

    CN114335581A

  • Functionalized single walled carbon nanotubes

    WO2006130150A2